2019
DOI: 10.1002/glia.23663
|View full text |Cite
|
Sign up to set email alerts
|

Neural sphingosine 1‐phosphate accumulation activates microglia and links impaired autophagy and inflammation

Abstract: Microglia mediated responses to neuronal damage in the form of neuroinflammation is a common thread propagating neuropathology. In this study, we investigated the microglial alterations occurring as a result of sphingosine 1‐phosphate (S1P) accumulation in neural cells. We evidenced increased microglial activation in the brains of neural S1P‐lyase (SGPL1) ablated mice (SGPL1fl/fl/Nes) as shown by an activated and deramified morphology and increased activation markers on microglia. In addition, an increase of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 66 publications
4
66
0
Order By: Relevance
“…Outside of the tumor setting, mice without S1P lyase expression had greater microglial activation in the brain. The accumulation of S1P signaled through S1PR2 to mediate this inflammation [ 160 ]. Figure 4 shows an overview of the alterations in both the adaptive and innate immune cells in GBM and metastatic cancers.…”
Section: Immune Traffickingmentioning
confidence: 99%
“…Outside of the tumor setting, mice without S1P lyase expression had greater microglial activation in the brain. The accumulation of S1P signaled through S1PR2 to mediate this inflammation [ 160 ]. Figure 4 shows an overview of the alterations in both the adaptive and innate immune cells in GBM and metastatic cancers.…”
Section: Immune Traffickingmentioning
confidence: 99%
“…SGPL1 deficiency in brain has been shown to affect neuronal health and to cause neuroinflammation accompanied by impairment of cognitive and motor skills in mice [ 17 , 18 , 28 ]. The central aim of the present study was to further unravel the molecular bases of the neurological phenotype of SGPL1 fl/fl/Nes mice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, apart from hyperphosphorylation, microglial activation and thus neuroinflammation appear to be essential for astrocytic tau pathology [ 30 ]. We have recently shown that in SGPL1 fl/fl/Nes mice, microglial activation and hence release of pro-inflammatory cytokines including interleukin (IL) 6 (IL-6) and tumor necrosis factor alpha (TNF-α), is caused by S1P released from SGPL1-deficient astrocytes [ 28 ]. Whether and how these factors are involved in the tau hyperphosphorylation of SGPL1-deficient astrocytes has to be clarified in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies have examined this mechanism in migraine. It is well documented that autophagic ux can affect the microglial phenotypes and guide the in ammation into a protective or detrimental state [123][124][125][126]. The enhanced autophagy has been reported to induce activation of M1 phenotype microglia and promote the release of pro-in ammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%